Potential of regenerative medicine for treatment of vitiligo patients - A. A. Kubanova; V. A. Volnukhin; D. V. Proshutinskaya; M. B. Zhilova; V. V. Chikin; A. E. Karamova; R. R. Saitburkhanov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents a review of publishes sources on the efficacy of methods such as tissue engineering and cellular transplantation of autologous melanocytes for treatment of vitiligo patients. The article describes general principles of treatment and particular features of current melanocyte transplantation methods.